RASIO LEVELTIROKSIN (T4) DAN TRIIODOTIRONIN (T3) PADA CAIRAN FOLIKEL SAPI BERFOLIKEL BESAR - , INTAN PURWANTI PUTRI NGAWITAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of the study was detect the ratio of T4:T3 in follicular fluid so it could be use as indicator of reproduction disruptions. The study used follicular fluid from 16 crossed Ongole local cattle (PO) ovarians. Ovarian samples were collected from slaughtered cattle in Rumah Potong Hewan (RPH) Giwangan. All follicles were measured and follicular fluid were taken and placed into effendorf tubes, after that the samples were sentrifugated 3000 rpm for 5 minutes. The samples was assayed using Enzyme-linked Immunosorbent Assay (ELISA) to know the level of T4 and T3 in the follicular fluid. The result showen that level T4 in follicular fluid were higher than level T3, it were 1,80 μg/mL ± 0,47 for T3 and 20,97 μg/mL ± 5,04 for T4. Ratio of T4:T3 that was 12,36 ± 3,9 the lower value is 7,31 whereas the higher value is 19,19.